Optimizing Law Enforcement in the Case of Online Gambling Promoters/Endorsements - Cokronegoro, Haryo; Prasetyo , Handoyo (Media Iuris, 2025)
This study aims to investigate strategies for optimizing law enforcement in cases of online gambling promoters or endorsements. The primary objective is to analyze the effectiveness of existing legal measures and explore potential improvements or innovations in law enforcement to address illegal online gambling promotions. The research method involves a literature review of case studies, comparative analysis, and a critical approach to existing legal regulations. Various related studies and literature will be analyzed to provide a comprehensive understanding of this issue. The analysis indicates that cooperation between regulators, law enforcement agencies, and social media platforms is key to enhancing law enforcement against online gambling promoters or endorsements. The need for stricter regulations, the implementation of technology for detection and prevention, and an emphasis on transparency in online gambling promotions are identified as crucial points to improve law enforcement. This study also highlights the importance of awareness of the ethical implications of online gambling promotions, especially those involving celebrity participation. In conclusion, this research proposes several law enforcement optimization strategies that should be implemented to reduce the illegal promotion of online gambling and protect the public from its negative impacts. These strategies are supported by strengthening regulations and cooperation between the government, law enforcement agencies, and the online gambling industry.